Investigation on Structural and Optical Properties of Willemite Doped Mn2+ Based Glass-Ceramics Prepared by Conventional Solid-State Method - Samsudin, Nur Farhana; Matori, Khamirul Amin; Liew, Josephine Ying Chi; Wing Fen, Yap; Mohd Zaid, Mohd Hafiz; Nadakkavil Alassan, Zarifah (Journal of Spectroscopy, 2015)
Mn-doped willemite (Zn2SiO4:Mn2+) glass-ceramics derived from ZnO-SLS glass system were prepared by a conventional melt-quenching technique followed by a controlled crystallization step employing the heat treatment process. Soda lime silica (SLS) glass waste, ZnO, and MnO were used as sources of silicon, zinc, and manganese, respectively. The obtained glass-ceramic samples were characterized using the X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), Fourier Transform Infrared (FTIR), UV-Visible (UV-Vis), and photoluminescence (PL) spectroscopy. The results of XRD revealed that ZnO crystal and willemite (β-Zn2SiO4) were presented as major embedded crystalline phases. This observation was consistent with the result of FESEM which showed the presence of irregularity in shape and size of willemite crystallites. FTIR spectroscopy exhibits the structural evolution of willemite based glass-ceramics. The optical band gap shows a decreasing trend as the Mn-doping content increased. Photoluminescent technique was applied to characterize the role of Mn2+ ions when entering the willemite glass-ceramic structure. By measuring the excitation and emission spectra, the main emission peak of the glass-ceramic samples located at a wavelength of 585 nm after subjecting to 260 nm excitations. The following results indicate that the obtained glass-ceramics can be applied as phosphor materials.